Determination of the average molecular weight of sodium polystyrenesulphonate from viscosity measurement - Bhattarai, Ajaya (Scientific World, 2012)
Precise measurements on the viscosity of aqueous solutions of sodium polystyrenesulphonate and in presence 0.1 N sodium chloride at 308.15 K were reported. The degree of substitution of sodium polystyrenesulphonate used was one. The sodium polystyrenesulphonate (NaPSS) used in these investigations was purchased from Aldrich Chemical Company, Inc. whose viscosity average molecular weight was 70,000. The experimental viscosity average molecular weight of polystyrenesulphonate was found 70,186.15. Scientific World, Vol. 10, No. 10, July 2012 p17-19 DOI: http://dx.doi.org/10.3126/sw.v10i10.6855